Facile and fast microwave-assisted fabrication of activated and porous carbon cloth composites with graphene and MnO2 for flexible asymmetric supercapacitors. (1st August 2018) - Jeon, Hyeonyeol; Jeong, Jae–Min; Hong, Seok Bok; Yang, MinHo; Park, Jeyoung; Kim, Do Hyun; Hwang, Sung Yeon; Choi, Bong Gill
Abstract: Current collectors and substrate materials are of pivotal importance for the design and preparation of electrodes and energy storage devices, because their surface areas, morphologies, ionic and electronic conductivities, and mechanical properties substantially influence electrochemical performances. Although carbon cloths (CCs) are widely considered the most promising current collectors for flexible energy storage devices, the majority of carbon-based textiles have poor capacitances due to their low surface areas and porosities, which reduce device performances. Here, we report a rapid and straightforward method for preparing CC-based electrode materials for high performance supercapacitors using microwaves. Microwave irradiation efficiently activates the surface pores of carbon fibers, and increases specific capacitance markedly as compared with pristine CC. In addition, surfaces of microwave-treated CCs (m-CCs) are coated with reduced graphene oxide (RGO) or MnO2, and the resulting electrode materials exhibit excellent electrochemical performances, such as, high specific capacitances, high rate capabilities, and long-term cycling stabilities. Flexible solid-state supercapacitor devices are fabricated using a RGO/m-CC as a negative electrode and a MnO2 /m-CC as a positive electrode. The produced asymmetric supercapacitors show an excellent resilience to harsh electrochemical and mechanical conditions, and high energy and power densities.